2015
DOI: 10.2310/7750.2014.14129
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Multinucleate Cell Angiohistiocytoma

Abstract: Overall, MCA is a poorly understood, distinct dermatologic phenomenon. Here we present a case of generalized MCA to further the understanding of this disease presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Vitiligo with anti‐thyroid antibodies in another patient, also anti‐Ro 60 and positive antinuclear antibodies were reported once . Primary biliary cholangitis, aortic and tricuspid valve replacements following endocarditis, diabetes and dyslipidemia were associated with MCAH in one patient . Also, the laboratory value of 17‐hydroxyprogesterone was elevated in one patient, and gastroesophageal reflux disease was reported in another .…”
Section: Literature Reviewmentioning
confidence: 90%
“…Vitiligo with anti‐thyroid antibodies in another patient, also anti‐Ro 60 and positive antinuclear antibodies were reported once . Primary biliary cholangitis, aortic and tricuspid valve replacements following endocarditis, diabetes and dyslipidemia were associated with MCAH in one patient . Also, the laboratory value of 17‐hydroxyprogesterone was elevated in one patient, and gastroesophageal reflux disease was reported in another .…”
Section: Literature Reviewmentioning
confidence: 90%
“…Some of the papules may coalesce to form larger annular lesions. [1][2][3][4][5][6] The existing literature shows most MCAHs occur in middle-to old-aged persons, affecting women more than men. In this 14-year-old boy case, the authors confirmed that MCAH can also occur in young age patients.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of clonality, several cases of spontaneous regression, and tendency to occur as multiple lesions usually at exposed areas vulnerable to trauma support the reactive condition hypothesis as being more plausible. 5 By comparing the microscopic and immunohistochemical findings of the papule (new lesion) and the plaque (old lesion), the authors could directly observe that the inflammatory response progresses during the course of MCAH.…”
Section: Discussionmentioning
confidence: 99%
“…11,15 The generalized variant is extremely rare, with only four cases recorded in the literature. Our patient present a localized form, with almost 40 lesions distributed exclusively on the lower limbs.…”
Section: Nevertheless the Immunochemistry For Eralpha Was Negative Inmentioning
confidence: 99%